A new bis-pyrazolylpyridine ruthenium(III) complex as a potential anticancer drug: in vitro and in vivo activity in murine colon cancer - Lazic, Dejan; Scheurer, Andreas; Cocic, Dusan; Milovanovic, Jelena; Arsenijevic, Aleksandar; Stojanovic, Bojana; Arsenijevic, Nebojsa; Milovanovic, Marija; Simovic, Ana Rilak (Dalton Transactions, 2021)
We synthesized and characterized the ruthenium(III) pincer-type complex [RuCl3(H2Lt-Bu] (H2Lt-Bu = 2,6-bis(5-tert-butyl-1H-pyrazol-3-yl)pyridine, 1) by elemental analysis, IR and UV-Vis spectroscopy, and the mass spectrometry (MS) method ESI Q-TOF. For comparison reasons, we also studied ruthenium(III) terpyridine complexes of the general formula [Ru(N-N-N)Cl-3], where N-N-N = 4'-chloro-terpyridine (Cl-tpy; 2) or 4'-chlorophenyl-terpyridine (Cl-Ph-tpy; 3). A kinetic study of the substitution reactions of 1-3 with biomolecules showed that the rate constants depend on the properties of the spectator ligand and the nature of the entering nucleophile. The DNA/HSA binding study showed that in comparison to complex 1 (bis-pyrazolylpyridine), the other two (2 and 3) terpyridine complexes had a slightly better binding affinity to calf thymus DNA (CT DNA), while in the case of human serum albumin (HSA), complex 1 exhibited the strongest quenching ability. We demonstrated that 1 possesses significant in vitro cytotoxic activity against mouse colon carcinoma CT26 cells and in vivo antitumor activity in murine heterotopic colon carcinoma. Complex 1 induced G0/G1 cell cycle arrest and apoptotic death in CT26 cells. Additionally, 1 showed anti-proliferative activity, as evaluated by the detection of the expression levels of the Ki67 protein. Furthermore, the in vivo results showed that 1 reduced primary tumour growth and the number and growth of lung and liver metastases, significantly prolonging the treated mice's survival rate. This study highlighted that 1 does not show hepato- and nephrotoxicity. Our data demonstrated the considerable antitumor activity of the ruthenium(iii) pincer complex against CT26 tumour cells and implicated further investigations of its role as a potential chemotherapeutic agent for colon carcinoma.
CRIS-Team WoS Importer:2021-05-28